Material Management Effectiveness - Natashia Angelina Theodara; Darmawan, Didit; Putra, Arif Rachman (Metromedia, 2022)
Material transfer is concerned with how best to move material from one place of the production process to another. Effective and necessary material transfer activities to accelerate production to distribution activities. Material handling includes various components to keep the supply chain running. The effectiveness of material handling can be realized if it follows the basic principles and all regulations are carried out by the relevant parties.